Neuroacanthocytosis. Issue 5 (1st October 2004) - Zeman, Adam; Shenton, Geoff
Abstract : INTRODUCTION Acanthocytes, from the Greek 'acantha' meaning thorn, are red blood cells with irregular thorn-like projections. They are easily confused with 'echinocytes' also known as 'burr cells', which occur in liver disease, uraemia and following splenectomy. Echinocytes have more regular projections and a broader base than acanthocytes (Fig. 1). Acanthocytes are not normally present in peripheral blood. Their detection requires careful, sometimes repeated, examination of blood smears. They are principally associated with three rare but fascinating neurological syndromes: choreoacanthocytosis, the McLeod syndrome and hypo- and abeta-lipoproteinaemia (Fig. 2). AN ILLUSTRATIVE CASE A 50-year-old unemployed man, who had been abnormally fidgety ever since childhood, was referred to the psychiatric services because of impulsive and disinhibited behaviour, for example going naked into his back garden and talking loudly to himself in public. He had been sleeping poorly. Furthermore, his wife reported that he been hoarding 'junk' in his house for many years.